2012
DOI: 10.2480/agrmet.68.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Poor grain growth in rice under high temperatures affected by water temperature during vegetative stage

Abstract: Poor grain growth caused by high temperatures during the ripening stage is a critical problem for rice production. However, the magnitude of the reduction in grain growth also depends on the temperatures before the ripening stage. We hypothesized that the water temperature (T w ) during vegetative growth can affect grain growth under high temperatures during the ripening stage. We exposed the japonica cultivar 'Hitomebore' to four levels of T w during vegetative growth, ranging from 20 to 30℃, and examined gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We found that large leaf areas couldn't generate a high yield. Probably, the green leaf area did not respond consistently to water temperature during vegetative growth and photosynthetic capacity would not increase under higher Tw during the vegetative stage [16]. So, the low yield on HH indicates the effect of high temperature in the process of supplying carbohydrates from leaves to grains.…”
Section: Production Of Rice and Its Componentsmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that large leaf areas couldn't generate a high yield. Probably, the green leaf area did not respond consistently to water temperature during vegetative growth and photosynthetic capacity would not increase under higher Tw during the vegetative stage [16]. So, the low yield on HH indicates the effect of high temperature in the process of supplying carbohydrates from leaves to grains.…”
Section: Production Of Rice and Its Componentsmentioning
confidence: 95%
“…We can see in Table 1 shows the heading stage on HH is faster than NM and HR, so the grain on HH is exposed to high temperatures. In terms of carbohydrates, water temperature during the vegetative stage [16] and sunlight during ripening [17] will affect seed growth. Moreover, grain growth during the ripening period is determined by the size of the hull and by the supply of carbohydrates to the grain, as well as the use of these carbohydrates [16].…”
Section: Production Of Rice and Its Componentsmentioning
confidence: 99%